Changes in the Number and Age Structure of the Population of the Northern Macroregion in the First Two Decades of the 21st Century - Majdzińska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
The main aim of the paper is to analyze the changes in the number and age structure of the northern macroregion population (formed by Pomorskie, Kujawsko‑Pomorskie, and Warmińsko‑Mazurskie voivodships) and their assessment in terms of the advancement of demographic old age in both decades of the 21st century. An additional goal was an analysis of the studied areas from the point of view of intensity of the factors of growth and decline in the population.The study employed relative indices, relative frequencies as well as fix base indices. The analyzes were based on the Central Statistical Office statistical data on the population structure by age, as well as the natural and migratory movement of the population in voivodships, poviats, and municipalities of the northern macroregion.In the northern macroregion, the advancement of demographic aging, as well as the intensity of natural and migratory population events, is highly diversified within regions. Relatively younger areas are mainly rural municipalities located near cities, while the oldest ones are mainly cities or municipalities located on the outskirts of voivodships or far away from cities. Relatively the most favorable demographic situation can be observed in the Pomorskie Voivodship, while the least favorable one in the Warmińsko‑Mazurskie Voivodship.